Symptom and Disability One Year After Traumatic Brain Injury - Sukraeny, Nury (South East Asia Nursing Research, 2019)
TBI is a leading cause of death and disability worldwide. The effects of TBI can significantly disrupt the lives of those who are injured and survive. TBI can affect patients in the physical, cognitive, behavioral and emotional domains which appear from the acute phase and can remain long-term. This cross sectional survey aimed to examine the disability after TBI by the components of ICF and also to describe the symptom present in one year after TBI. TBI patients were recruited from the medical record data of patients admitted to the neurosurgery unit who at least 12 month after discharge from hospital and able to be followed up. The DRS was used for measured disability. Total 56 TBI patients were recruited in this study, 58.9% of the subjects were classified as mild TBI, while 37.5% and 3.6% of them were classified as moderate and severe TBI respectively. More than half of subjects (62.5%) reported of current symptoms with headache as a most common reported. Based on DRS was found that 83.9% of the subjects have no disability, whereas 3.6% had a mild disability, 5.45 had a partial disability, and 7.2% had a moderate disability. The results demonstrated that a TBI survivors face substantial disability and symptom 1 year after injury. To optimise health and well-being outcomes, clinicians need to identified the needs of patients with less severe TBI and treated during the post-acute period.